STRUKTUR ANATOMI DAN AKTIVITAS ANTIOKSIDAN BULBUS BAWANG DAYAK (Eleutherine americana MERR.) DARI DAERAH KALIMANTAN SELATAN - Evi Mintowati Kuntorini; Maria Dewi Astuti; L. Hartanto Nugroho (The East Java Biological Society, 2010)
The aim of this research were to study the characterization of the microscopic anatomy and testing the antioxidant activity of bawang dayak bulb from several regions in South Kalimantan. Bawang dayak plant samples taken from four (4) regency in South Kalimantan. Bulb anatomical structure was observed by the paraffin method and test preparations of antioxidant activity by DPPH method. IC50 values were calculated based on the formula of the regression equation.The bulb anatomical structures has an epidermis tissue of both surfaces, there is parenchymal tissue. Transport tissue were located in rows with collateral type, there are starch grains in parenchyma cells, and the presence of stiloid crystals between cells parenkim. Extract ethanol bawang dayak bulb from the four districts in South Kalimantan has antioxidant activity against DPPH radicals. The highest antioxidant activity showed on the sample from location1 Comets Village Banjarbaru Municipality (IC50 = 25.3339 μg/ml) and the lowest showed on the sample from location 2 Sungai Paring Village Banjar District (IC50 = 86.9039 μg/ml). Antioxidant activity of bawang dayak extract 4.5 to 15 times weaker compared to BHT (BHT IC50 = 5.5707 μg/ml).